Análise da expressão de UCP2 no estresse oxidativo e apoptose em ratos submetidos à epilepsia experimental induzida pela pilocarpina - Dutra, Marina Rascio Henriques (2019)
Epilepsy is a chronic brain disorder characterized by the recurrence of unprovoked epileptic seizures, studies report that nearly 1% of people experience a seizure during their lives and affects around 65 million people worldwide, with the most common neurological disease , chronic and dangerous epilepsy of the Mesial Temporal Lobe (ELTM) where the patient may present simple or complex focal seizures that originate from the temporal lobe, some mechanisms that lead to this disorder include the imbalance of voltage-dependent ion channels, activation of AKT phosphorylation through the production of reactive oxygen species (EROs). Epilepsy has great clinical relevance due to its high incidence and severity, as well as its social reason which, in severe cases, impedes the patient's social interaction. a desirable process in many neurological disorders, but the complex mechanisms involved in this field are not completely understood. Mitochondria are the main regulators of cellular energy metabolism (MS), through the production of Adenosine triphosphate (ATP), the Decoupling Proteins (UCPs) are present in the inner membrane of the mitochondria and act regulating the electron transport chain, stimulus for the production of reactive oxygen species (ROS), thus relieving cellular damage during epileptic seizures. The model of pilocarpine epilepsy resembles human ELTM being characterized by the prevalence of epleticus (SE) status and incite the increase of the ROS production, besides causing a powerful cellular death by excitotoxicity induced by convulsions, due to the excessive production of ROS , and mitochondrial impairment is notably observed in this model. The anti-sense Oligonucleotide (ASO) treatment was used in this work, in order to take advantage of its characteristic of preventing the production of the protein of the gene that targets, through blocking the translation of the mRNA, this tool was used in these animals to prevent the production of UCP2 in order to clarify the role of UCP2 in the epileptic disorder, thus discovering that UCP2 acts to inhibit mechanisms of apoptotic factors and oxidative stress to increase survival of neurons after the onset of ES. The present study had as main objective to investigate the role of UCP2, a negative regulator of EROs, in the neuroprotection after cholinergic insult, mimicked by the action of pilocarpine. In order to arrive at the decision on which time of epilepsy the expression of UCP2 would have, in order to block it, a protocol of observation of the stages of the disease was made to determine in which one of them there is UCP2 expression, followed by another experimental group, where we evaluated the temporal course in order to clarify the moment in which we would have the peak of its expression. After these two processes we finally determine the best time for ASO administration. Our data demonstrated that increased UCP2 expression in the rat hippocampus begins after 3 days of the induction of the status epilepticus (SE), reaching peak expression at 5 days after SE, which corresponds to the latent phase of epilepsy, after that period levels return to baseline. Concomitantly, phospho-AKT expression levels were higher in the hippocampus during the early silent phase (5 days after SE). In addition, UCP2 blocking by anti-sense oligonucleotides (ASO) in SE mice has been shown to successfully decrease both the mCPNA and protein content of UCP2. The treatment with ASO in these animals increased the pro-apoptotic mitochondrial factors, the activity of caspase 3, the expression of inflammatory cytokines, the activities of the antioxidant enzymes and the formation of ROS. In conclusion, the present results highlight the neuroprotective actions of UCP2, acting through inhibition of apoptotic factors and oxidative stress, to increase survival of neurons after ES onset.